2010
DOI: 10.1051/0004-6361/201015099
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the [C II] emission in the S140 photon-dominated regions. New insights from HIFI

Abstract: Using Herschel's HIFI instrument, we observe [C ii] along a cut through S140, as well as high-J transitions of CO and HCO + at two positions on the cut, corresponding to the externally irradiated ionization front and the embedded massive star-forming core IRS1. The HIFI data were combined with available ground-based observations and modeled using the KOSMA-τ model for photon-dominated regions (PDRs). We derive the physical conditions in S140 and in particular the origin of [C ii] emission around IRS1. We ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The significant difference in the velocity profile of the [C ii] emission observed in many sources is interpreted as an indication of a substantial fraction of the [C ii] emitting material being accelerated relative to the quiescent material, e.g. it undergoes ablation (Dedes et al 2010;Mookerjea et al 2012;Okada et al 2012;Schneider et al 2012;Simon et al 2012;Pilleri et al 2012), or photoevaporated (Sandell et al 2015). Although an order of a few km s −1 displacement is consistent with modeled photoevaporation in globules (Lefloch & Lazareff 1994), only a few studies to compare the observed line profiles of different emission lines with simulation incorporating full PDR chemistry have been conducted (Bisbas et al 2018).…”
Section: Line Profiles Of Co [C I] [C Ii] and [O I]mentioning
confidence: 99%
“…The significant difference in the velocity profile of the [C ii] emission observed in many sources is interpreted as an indication of a substantial fraction of the [C ii] emitting material being accelerated relative to the quiescent material, e.g. it undergoes ablation (Dedes et al 2010;Mookerjea et al 2012;Okada et al 2012;Schneider et al 2012;Simon et al 2012;Pilleri et al 2012), or photoevaporated (Sandell et al 2015). Although an order of a few km s −1 displacement is consistent with modeled photoevaporation in globules (Lefloch & Lazareff 1994), only a few studies to compare the observed line profiles of different emission lines with simulation incorporating full PDR chemistry have been conducted (Bisbas et al 2018).…”
Section: Line Profiles Of Co [C I] [C Ii] and [O I]mentioning
confidence: 99%
“…The deconvolved [C ii] line width in most regions is narrower than the PACS instrumental profile at 157 μm (FWHM = 240 km s −1 ); thus, line widths in our data are dominated by the instrumental profile. Observations of [C ii] emission in a galactic star-forming region and its associated PDR show widths of 5-10 km s −1 using the Heterodyne Instrument for the Far Infrared (HIFI) on Herschel's (Dedes et al 2010), which has a velocity resolution of 0.7 km s −1 . For narrow [C ii] emission, i.e., 4-10 km s −1 , the [C ii] line becomes optically thick at N(H) = 3.65-6.25 × 10 21 cm −2 (Russell et al 1980), assuming N (C + )/N(H) = 1.6 × 10 −4 .…”
Section: Self-absorbed Optically Thick [C Ii]mentioning
confidence: 99%
“…Habart et al (2011) found order-of-magnitude discrepancies between their PDR model results and Spitzer H 2 data for rotational levels J 3 toward mainly low-excitation PDRs. Dedes et al (2010) were able to fit observations of high-J CO lines by using spherical PDR models for an ensemble of clumps distributed in size and mass. Weingartner & Draine (1999) have suggested that radiation forces on grains increase the dust/gas ratio in PDRs, thus leading to enhanced heating rates.…”
Section: Introductionmentioning
confidence: 99%